(3TQGFY GdESdGes - (3GdeMbb GdMdj , LYaQ Hf GdMSf Hf jMji Hf GdMSjf Hf SYjO GdgPdj, fLe GdOjf CHh GdbGSe,J (B676 (3g` s
(3ChdgG (B:s
(3GdeGA cdg WGgQ ef ddMOK hGdNHK hGdfLGSI s
(3BNQgG (B:s
(3eKdeG bGd GdTjN de jYbd Yfg GdeSdehf ef YUHJg hdG GddZGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B137s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B43s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis